Social Deixis in Students’ Writing: A Case Study of Indonesian Secondary Students - Ika Lusi Kristanti; Afi Ni'amah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
The social position or role of participants in communicative events is referred to as social deixis. The parts of language structure that encode individuals' social identities are referred to as social deixis. The current study examined the use of social deixis in students’ writing. It focused on secondary students’ writing. The students were allowed to choose the topic of writing. Using qualitative research, this study  collected the data through documentation. The data were analyzed through data condensation, data display, drawing, and conclusion. The findings revealed that students' writing only contained relational social discourse. The students' writing frequently used addressee honorific relational social discourse. For the purpose of showing respect, students frequently used relational social deduction. Readers are persuaded to do a particular action by the students' goal as well.